2003
DOI: 10.1182/blood-2002-12-3737
|View full text |Cite
|
Sign up to set email alerts
|

The role of autocrine FGF-2 in the distinctive bone marrow fibrosis of hairy-cell leukemia (HCL)

Abstract: Bone marrow (BM) fibrosis is a central diagnostic and pathogenetic feature of hairy-cell leukemia (HCL). It is known that fibronectin (FN) produced and assembled by the malignant hairy cells (HCs) themselves is a major component of this fibrosis. It is also known that FN production is greatly enhanced by adhesion of HCs to hyaluronan (HA) via CD44. The aim of the present study was to establish the roles of fibrogenic autocrine cytokines (fibroblast growth factor-2 [FGF-2] and transforming growth factor ␤ [TGF␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 24 publications
1
34
0
1
Order By: Relevance
“…However, in comparison to other established breast cancer cell lines, IPH-926 cells did not display significant overexpression of FGFR1 mRNA ( Figure 7D). In fact, FGFR1 protein expression was barely detectable in IPH-926 cells by western blotting of 30 µg of total cellular proteins separated by SDS-PAGE using the well-established monoclonal anti-FGFR1 antibody M19B2 ( Figure 7E) [44]. This was additionally confirmed with another anti-FGFR1 antibody, 10646, whose specificity has also previously been demonstrated ( Figure 7F) [10].…”
Section: Comparison Of Iph-926 and Mda-mb-134supporting
confidence: 71%
“…However, in comparison to other established breast cancer cell lines, IPH-926 cells did not display significant overexpression of FGFR1 mRNA ( Figure 7D). In fact, FGFR1 protein expression was barely detectable in IPH-926 cells by western blotting of 30 µg of total cellular proteins separated by SDS-PAGE using the well-established monoclonal anti-FGFR1 antibody M19B2 ( Figure 7E) [44]. This was additionally confirmed with another anti-FGFR1 antibody, 10646, whose specificity has also previously been demonstrated ( Figure 7F) [10].…”
Section: Comparison Of Iph-926 and Mda-mb-134supporting
confidence: 71%
“…[6][7][8] Although the results were somewhat conflicting in regard to FGFR expression patterns for each cell line, the data suggest that most AML cell lines express at least one of the four FGFRs. Because of the typically low receptor density of tyrosine kinase receptors, detection on a protein level by standard methods such as flow cytometry 20 or Western blot without immunoprecipitation has been a daunting task. In addition, FGFRs may be cleaved 21 and/or internalized 22 as part of the signaling mechanism, further complicating receptor detection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reticulin fibrosis, it has been recently demonstrated that the glycoprotein fibronectin, which is produced and assembled by HCs, contributes to the fibrotic process in BM of HCL patients (19). This process was also found to be particularly enhanced by bFGF, which is endogenously produced by the HCs (20). Since reticulin and fibronectin fibers were found to represent different structures in myelofibrotic BM (21), it appears that BM fibrosis in HCL is a complex process that involves accumulation and assembly of collagenous ECM components (reticulin) (22) and noncollagenous ECM components (fibronectin).…”
Section: Introductionmentioning
confidence: 95%